Real-time systems - Krishna, C.M.; Shin, Kang G. (New York : McGraw-Hill, 1997)
Introduction. Characterizing real- time systems and tasks. Task assignment and scheduling. Programming languages and tools. Real-time databases. Real-time communication. Fault-tolerance techniques. Reliability Evaluation techniques. Clock synchronization.
Keywords: Computers; Real-time data processing; Real-time control